Predicting Super Bowl Ad Likeability in the New Millennium - Hofer, Ashley; Rozumalski, Dan; Theiler, Clay (My University, 2010)
U.S. advertisers love the Super Bowl because it reaches a huge and highly receptive audience. One metric Super Bowl advertisers watch closely is ad likeability, since this is correlated with sales success. This study is a replication and extension of the 2001 Tomkovick, Yelkur, and Christians research of Super Bowl ads in the 1990s. We explored 488 ads from the nine Super Bowls during the years 2000-2008. Our findings show humor, animals, product category, product information and presence of children all significantly impacted ad likeability.
Color poster with text, images, and graph.
Keywords: Television advertising--Evaluation; Advertising in popular culture--Evaluation; Super Bowl--Advertising--Evaluation; Posters